2016
DOI: 10.1183/13993003.01229-2016
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly in sleep apnoea patients: a large observational study of 755 patients

Abstract: Polycyclic aromatic hydrocarbons (PAHs) at traffic and urban background sites of northern Greece: source apportionment of ambient PAH levels and PAH-induced lung cancer risk. Environ Sci Pollut Res Int 2016; 23: 3556-3568. 13 Tsiligianni IG. COPD patients trapped in the financial crisis in rural Crete. Lancet Respir Med 2013; 1: e31-e32. 14 Bakogeorgos M, Mountzios G, Bournakis E, et al. Do elderly patients with non-small cell lung cancer get the best out of recent advances in first-line treatment? A comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
4
24
0
2
Order By: Relevance
“…We analysed data from the French national sleep apnoea registry 'Observatoire Sommeil de la Fédération de Pneumologie' (OSFP) (www.osfp.fr). 9,11,12 The webbased OSFP registry, administered by the French Federation of Pulmonology, contains anonymized longitudinal data from patients complaining of sleep disorders reported by respiratory physicians in private practice, general and university hospitals. Periodic quality controls ensure up-to-standard data recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed data from the French national sleep apnoea registry 'Observatoire Sommeil de la Fédération de Pneumologie' (OSFP) (www.osfp.fr). 9,11,12 The webbased OSFP registry, administered by the French Federation of Pulmonology, contains anonymized longitudinal data from patients complaining of sleep disorders reported by respiratory physicians in private practice, general and university hospitals. Periodic quality controls ensure up-to-standard data recording.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment-emergent CSA was associated with a higher risk of therapy discontinuation. 10 In this large real-life study using CPAP device-generated data, only age and gender were available and it was not possible to determine the role of co-morbidities, indices or OSA severity and the potential impact of various technical aspects of CPAP management 9,11,12 including that of interfaces. 13 Our hypothesis was that the underlying co-morbidities, especially cardiovascular diseases, lifestyle, OSA characteristics at diagnosis and type of interface, might explain persistent AHI > 5 during CPAP use.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep apnea syndrome, mostly the obstructive type (OSAS), is a frequent comorbidity in acromegaly (reported mean, 69%, with a wide range, i.e . 27-100%) [ 55 ]; therefore all acromegaly patients should undergo a sleep study at diagnosis to be repeated during follow-up if pathological [ 53 , 56 ]. Sleep study should be quickly offered above all to symptomatic patients, patients with obesity or severe cardiovascular comorbidities, and patients at risk of accidents due to their work [ 57 , 58 ].…”
Section: Clinical Issuesmentioning
confidence: 99%
“…The estimated prevalence is 40 to 125 cases per million according to different epidemiological studies [ 4 8 ], but recent population based studies have shown that prevalence could be 5 to 15 times higher [ 9 13 ]. Schneider et al, in an unselected German population from a primary care center, found a prevalence of 1000 cases per million (1/1000) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors showed that the probability of acromegaly in a hypertensive population without acral enlargement was very unlikely [ 12 ]. Recently, Galerneau et al described the prevalence of acromegaly in unselected patients with suspected sleep apnea-hypopnea syndrome (SAHS) and fount it to be 2.5/1000 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%